Global burden and trends of firearm violence in 204 countries/territories from 1990 to 2019 - Ou, Zejin; Ren, Yixian; Duan, Danping; Tang, Shihao; Zhu, Shaofang; Feng, Kexin; Zhang, Jinwei; Liang, Jiabin; Su, Yiwei; Zhang, Yuxia; Cui, Jiaxin; Chen, Yuquan; et al. (Frontiers in Public Health, 2022)
Background Gaps remained in the updated information of the FV burden from a global landscape. Understanding the global burden of FV could contribute to decision-making. Methods Data on the FV burden, including physical violence by firearm (PVF), self-harm by firearm (SHF), and unintentional firearm injuries (UFI), were extracted from the Global Burden of Disease 2019. The temporal trends of age-standardized rate (ASR) were estimated using estimated annual percentage change (EAPC). Results In 2019, PVF, SHF, and UFI respectively reported 710.64×103, 335.25×103, and 2133.88×103 incident cases worldwide. Their ASR (/100,000 people-years) were 9.31, 4.05, and 29.07. During 1990-2019, the overall incident ASRs of PVF presented an increasing trend (EAPC = 0.61, 95% confidence interval [CI], 0.48 to 0.75). Notably, pronounced increasing trends were observed in Tropical Latin America, and North Africa and Middle East. However, incident trends of SHF and UFI declined globally, with the respective EAPCs being -0.68 (95%CI, -0.83 to -0.54) and -0.98 (95%CI, -1.19 to -0.77). In 2019, the ASR of death due to PVF, SHF, and UFI were 2.23, 0.65, and 0.26; and that of DALYs were 127.56, 28.10, and 17.64, respectively. Decreasing trends in the ASRs of FV were observed in most regions and countries worldwide over the past three decades, particularly that of PVF in Estonia. Conclusions the FV burden was heterogeneous across regions and countries, which was deeply subjected to socioeconomic factors. The findings highlighted that specific prevention strategies and interventions were required, particularly in the high prevalent settings.